EFEKTIVITAS MEDIA SOSIAL SEBAGAI SISTEM INFORMASI MANAJEMEN SEKOLAH - Setiawan, Dani; Hidayati, Dian (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The existence of social media such as Instagram, WhatsApp, Facebook, Youtube, Tik Tok and websites in this globalization era is very popular. If the school uses and manages it properly, it will assist in implementing the school management information system. However, several schools in the city of Bandung have not been able to use social media properly. Even though every school has social media that can be used as an information medium to socialize school programs to the community. One of the inhibiting factors is the limited school finances and the competence of school human resources in managing social media as a school management information system. The purpose of this research is to determine the effectiveness of social media as a school management information system. The method used in this study is qualitative with a qualitative descriptive approach, and data collection techniques through observation, interviews and documentation. Based on the results of the research, it shows that the use of social media by SMP Muhammadiyah 8 Bandung as a management information system is quite effective.